MOVIE- MEDIATED PRONUNCIATION LEARNING: EFL UNIVERSITY LEARNERS’ PERCEPTIONS - Anindya Dewi Agatha; Dadang Danugiri; Mobit Mobit (IKIP Siliwangi, 2023)
This study aims to know about the EFL student’s perception in learning pronunciation movie-assisted and the impact of English movie for learning pronunciation. The researcher uses interview as a research design. By using interview, the researcher investigate students’ perceptions during learning pronunciation activities movie-mediated. Then, the data obtained were analyzed. The results showed that students' perceptions and impact of movie-mediated learning pronunciation. The impact movie-mediated learning for EFL students is increasing the student’s vocabulary knowledge. Based on these findings, it can be concluded that most students can learn pronunciation by themself through movie-mediated learning. Movie-mediated learning is increase their vocabulary knowledge and how to pronounce it through the dialogue on the movie. The students also perceived that learning pronunciation movie-assisted was not enough with one movie, they need more than one movie to make the learning process more comprehensive.